Robot Troli Pengikut Pelanggan Otomatis Berbasis Image Processing - Nussy, Canis Andre; Hartono, Rodi (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2018)
Abstract - This research presents information about automatic trolley robot customer followers of image processing and microcontrollers. Generally, when we shopping at supermarkets usually provided baskets and trolleys to carry their groceries. Usually customers are required to drive the trolley or bring their own basket, so customers still feel troubled if they have to choose groceries while pushing the luggage cart. Of these problems came the idea of integrating between conventional trolleys and automation technology. The aim of the author making research about this robot trolley to make it easier and more convenient for supermarket customers to shop and carry their groceries. Where trolleys are made capable of following the movements of users without the need to slot deposit 5000 push them so that customers just have to buy items that are purchased and customers can walk in front of their shopping trolleys. The additional devices needed to drive the trolley automatically include camera, microcontroller, DC motor, servo motor, motorbike driver, and battery installed on the trolley. Image processing uses a camera on the system that is made to work by detecting the color of the object that has been determined to determine the distance of the object with the trolley. The method used to process image processing is a hue-based color filtering algorithm hue-based color filtering. So that the use of trolleys can move automatically to follow customers. The end result of this automatic follower trolley design is an 80% success rate with the maximum distance between objects and trolleys is 5.65m.Keyword : camera, image processing, microcontroller, DC motor.